Translation, cultural adaptation, and psychometric evaluation of the Patient Assessment Chronic Illness Care tool in Ethiopia (PACIC-5As-ET) for patients with type 2 diabetes - Yohannes Mulu Ferede; Margareta Westerbotn; Mignote Hailu Gebrie; Debrework Tesgera Beshah; Kerstin Erlandsson (PLoS ONE, 2026)
Introduction Chronic conditions are a significant global health challenge that adversely affects the quality of care for patients with type 2 diabetes (T2D). To evaluate and improve the quality of care, the Patient Assessment Chronic Illness Care (PACIC-5As) tool has been developed. It is the most widely used tool designed to assess the perceived quality of care among individuals with chronic conditions, including diabetes. Nevertheless, it has not yet been culturally adapted and validated in the Ethiopian context. Therefore, this study aimed to translate, culturally adapt, and evaluate the psychometric properties of the PACIC-5As tool in Ethiopia. Methods A multicenter cross-sectional study was conducted among individuals with type 2 diabetes from March 24, 2025, to May 5, 2025, in the Amhara region’s comprehensive specialized referral hospitals. A systematic random sampling technique was used to select the study participants. Data were collected through face-to-face interviews. The tool consists of 26 items and 5 domains. Content validity was assessed at both the individual and scale levels. Internal consistency was evaluated using Cronbach’s alpha (α) and composite reliability (CR), with a value ≥ 0.70 considered acceptable. Confirmatory factor analysis (CFA) was conducted to evaluate model fit and factor structure. Model fit was assessed using the absolute and incremental fit indices and interpreted based on the recommended thresholds. Convergent validity was computed using average variance extracted (AVE), with a value ≥ 0.4 considered adequate, while discriminant validity was evaluated using AVE and inter-construct correlations. Results A total of 520 study participants were enrolled, and 517 (99.4%) were included in the study. The overall mean summary score of PACIC-5As-ET was 2.68 (±0.62). The content validity index at the item and scale levels ranged from 80% to 100%, with an inter-rater agreement of 95%. The Cronbach’s alpha and composite reliability (CR) of the PACIC-5As-ET were 0.93. The Cronbach’s alpha values for the subscales ranged from 0.71 (Assist) to 0.82 (Arrange). The test-retest reliability of PACIC-5As-ET was 0.94. The model fit indices were χ²/df (2.79), RMSEA (0.06), SRMR (0.08), GFI (0.89), and CFI (0.40). The AVE value of the overall PACIC-5As-ET was 0.93, and the subscales ranged from 0.47 (Advise) to 0.59 (Arrange). Conclusions The Amharic version of the PACIC-5As-ET tool demonstrated excellent internal consistency and acceptable validity for assessing the perceptions of patients with T2D. The absolute fit indices were generally within the recommended range, whereas the incremental fit indices were low. Therefore, support for the hypothesized five-factor structure is limited and should be interpreted with caution.